Komunikasi Tokoh Introvert dan Ekstrovert dalam Serial Drama Korea - Tsanyta Zahra Istighfarina; Ratri Rizki Kusumalestari (Bandung Conference Series: Journalism, 2024)
Abstract. Drama series is one of the mass communication media that can package communication messages uniquely. My Liberation Notes is a South Korean drama series that tells the realistic daily life of three siblings by highlighting the personality differences of introverted and extroverted characters. In our society, there are misconceptions that judge a person's communication skills based on personality type. This study aims to determine the communication portrayed by characters with introverted and extroverted personalities in the drama series My Liberation Notes in intrapersonal, interpersonal, and group forms. The method used in this research is qualitative method with narrative approach of Seymour Chatman model through action, event, character, and setting components. The results show that introverted characters dominate intrapersonal communication scenes, while extroverted characters dominate group communication scenes. However, in the form of interpersonal communication, both introverted and extroverted characters portray a balanced role in the interaction scene between individuals. The characteristics of introverted characters tend to be closed, like to be alone, and a small circle of friends, while the characteristics of extroverted characters tend to be open or sensitive to the surrounding environment, adaptable, and happy to socialize in a large circle of friends. In the communication process, introverted characters portray individuals who think a lot before acting so that they are more careful in speaking and become creative and imaginative individuals. On the other hand, extroverts portray individuals who speak or act before thinking and are confident, assertive, and like to lead. Abstrak. Serial drama merupakan salah satu media komunikasi massa yang dapat mengemas pesan komunikasi secara unik. My Liberation Notes adalah salah satu serial drama asal Korea Selatan yang menceritakan keseharian realistis dari tiga bersaudara dengan menonjolkan perbedaan kepribadian tokoh introvert dan ekstrovert. Di masyarakat kita, terdapat miskonsepsi yang menilai kemampuan komunikasi seseorang berdasarkan tipe kepribadian. Penelitian ini bertujuan untuk mengetahui komunikasi yang digambarkan oleh tokoh dengan kepribadian introvert dan ekstrovert dalam serial drama My Liberation Notes dalam bentuk intrapersonal, interpersonal, dan kelompok. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan naratif model Seymour Chatman melalui komponen aksi, kejadian, karakter, dan latar. Hasil penelitian menunjukkan bahwa tokoh introvert lebih mendominasi scene komunikasi intrapersonal, sedangkan tokoh ekstrovert lebih mendominasi scene komunikasi kelompok. Namun, dalam bentuk komunikasi interpersonal, baik tokoh introvert maupun tokoh ekstrovert menggambarkan peran yang seimbang dalam scene interaksi antar individu. Karakteristik tokoh introvert cenderung tertutup, menyukai kesendirian, dan lingkup pertemanan yang kecil, sedangkan karakteristik tokoh ekstrovert cenderung terbuka atau peka dengan lingkungan sekitarnya, mudah beradaptasi, dan senang bersosialisasi di lingkup pertemanan besar. Dalam proses komunikasi, tokoh introvert menggambarkan individu yang banyak berpikir sebelum bertindak sehingga mereka lebih berhati-hati dalam berbicara serta menjadi individu yang kreatif dan imajinatif. Di sisi lain, tokoh ekstrovert menggambarkan individu yang berbicara atau bertindak sebelum berpikir panjang dan memiliki sifat percaya diri, tegas, dan senang memimpin.